Frequência e fatores associados à contaminação de pêlo de cães por ovos de Toxocara spp. na região de Presidente Prudente, São Paulo - MERIGUETI, Yslla Fernanda Fitz Balo (2017)
Toxocariasis is one of the most prevalent parasitic zoonoses in the world. The disease can present visceral, ocular, and neurotoxocariasis forms, and is principally caused by the nematode Toxocara canis, whose definitive host is the dog. The transmission of toxocariasis to humans is caused by accidental ingestion of larval eggs of the parasite, present in the soil. Studies have shown that dog hair has the capacity to harbor eggs of the parasite and represents a risk for transmission of the zoonosis. The objective of the present study was to evaluate the frequency and factors associated with the contamination of dog hair by Toxocara spp. of animals attended and/or abandoned at a Veterinary School Hospital in the western region of the State of São Paulo, Brazil. The hair samples were collected from the perineal region, and upper and lower tail regions. For analysis of the samples and recovery of Toxocara spp., the material was washed in Tween 20 and then filtered through sieves of 300µm, 212µm, and 38µm. Hair samples from 165 dogs were analyzed (23.0% abandoned and 77.0% domiciled dogs). Of the analyzed samples, 59 (35.8%) were from puppies and 106 (64.2%) from adult animals. In the sample evaluation, 6.7% of the dogs (11/165) were contaminated, with a mean of 12.2 eggs per animal (1-70 eggs/animal) and 57.5 eggs/gram of hair. There was an association between the presence of eggs in the hair and the animal being a puppy, abandoned, with no defined breed. Deworming was a protective factor for hair contamination. All animals with the presence of eggs in the hair presented with diarrhea/soft feces. Of the recovered eggs, all presented characteristics of viability. The perineal region was the most commonly contaminated (72.4%).The results demonstrate that the eggs of Toxocara spp. can be eliminated in the feces and can adhere to the surface of the hair of dogs, where they embryonate, mainly in puppies, non-domiciled dogs, dogs that are not dewormed, and those with short hair. Thus, prophylactic anthelmintic treatment and correct care regarding the hygiene of animals, especially in the first months of life, become essential to reduce the risk of transmission of toxocariasis to humans through direct contact with dogs.